Assessment of preferred methods to measure insulin resistance in Asian patients with hypertension. Issue 3 (7th January 2021) - Minh, Huynh Van; Tien, Hoang Anh; Sinh, Cao Thuc; Thang, Doan Chi; Chen, Chen‐Huan; Tay, Jam Chin; Siddique, Saulat; Wang, Tzung‐Dau; Sogunuru, Guru Prasad; Chia, Yook‐Chin; Kario, Kazuomi
Abstract: Insulin resistance (IR), a metabolic risk factor, is linked to the pathogenetic mechanism of primary hypertension. Detecting IR in the patients with hypertension will help to predict and stratify the added cardiovascular risk, institute appropriate IR management, and manage hypertension optimally. There are many methods for assessing IR, each with distinct advantages and disadvantages. The euglycemic insulin clamp and intravenous glucose tolerance test, gold standards for measuring IR, are used in research but not in clinical practice. Homeostatic model assessment (HOMA‐IR), a method for assessing β‐cell function and IR, is frequently applied presently, particularly in Asia. Besides, the triglyceride–glucose index (TyG) first published by South American authors showed a good correlation with the insulin clamp technique and HOMA‐IR index. This simple, convenient, and low‐cost TyG index is of research interest in many countries in Asia and can be used to screen for IR in the Asian hypertensive community.